137:oral Taking a chance on health: the lottery principle, healthcare resource allocation, and orphan drugs. (28th April 2022) - Bond, Ken; Sandman, Lars; Gustavsson, Erik
Abstract : When people have equal claims to a non-divisible good, such as a life-saving drug or ventilator, a lottery procedure is sometimes used to 'break the tie' and determine who receives the good. However, within the context of healthcare resource allocation decisions, a lottery seems to do much more than provide a unique tie-breaking mechanism: it accounts for considerations of equal moral worth, promoting distributive fairness by providing equal chances to potential recipients, and procedural fairness by ensuring impartiality and transparency in the allocation decision. The so-called lottery principle, then, appears to be an important principle among other consequentialist and non-consequentialist principles, such as capacity to benefit, life-years saved, and severity, that ought to be considered when making resource allocation decisions. This talk explores the consequences for moral deliberation of taking the lottery principle seriously as an expression of these values, and raises questions about its typical role as the last principle among many when deciding how to distribute scarce resources. The talk will explore questions such as how we ought to think about the lottery principle and its role within typical principlist decision approaches, such as balancing and lexical ordering, and how the relevance of the lottery principle may vary depending on the type of scarcity motivating the allocation decision, for example, when allocating ICU resources during a pandemic and prioritizing high-cost health care technologies. What constraints, if any, ought to be placed on the use of lotteries in these different contexts? While clarifying the role that the lottery principle might play, we conclude that, depending on the consequences one is willing to accept, the lottery principle should play either a larger or more restricted role in allocation decisions than is generally held.